(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
In an increasingly globalized world, linguistic proficiency is rapidly becoming a critical skill for future generations. This article addresses the challenges inherent in vocabulary acquisition, offering a curated selection of online resources designed to streamline and simplify the process of lexical expansion for learners struggling to build their vocabulary.